Healthcare-worker-associated outbreak of Panton–Valentine-leukocidin-producing meticillin-sensitive Staphylococcus aureus in a large neonatal unit in London: successful targeted suppression therapy following failure of mass suppression therapy. (April 2022) - Hatcher, J.; Godambe, S.; Lyall, H.; Tyszczuk, L.; Stubbs, F.; Cummings, N.; Sheils, K.; Hughes, C.; Kadhani, T.; Atkin, S.; Elaby, N.; Pichon, B.; et al.
Summary: Background: Staphylococcus aureus is a leading cause of healthcare-associated infection, and outbreaks have been associated with neonatal units and colonization of healthcare workers. Aim: To describe an outbreak of Panton–Valentine-leukocidin-producing meticillin-sensitive Staphylococcus aureus (PVL-MSSA) in a neonatal intensive care unit. Methods: Multi-disciplinary outbreak control investigation. Results: Over a period of 16 months, seven neonates were identified as positive for PVL-MSSA. Isolates were identified in blood cultures (two patients), nasopharyngeal aspirate (one patient) and rectal screening swabs (four patients). Epidemiological and whole-genome sequencing data suggested a long-term carrier as the most likely source. Despite two rounds of mass suppression therapy of staff, using chlorhexidine initially followed by octenidine-based regimens, positive patients continued to be identified. Staff screening subsequently identified one healthcare worker colonized with the outbreak strain of PVL-MSSA who underwent enhanced screening and further suppression therapy. No further cases have been identified to date. Compliance with mass suppression therapy was >95% and a post-administration staff satisfaction survey showed that the majority of staff agreed with the steps taken, with low rates of adverse reactions. Conclusion: S. aureus outbreaks are commonly associated with colonization of healthcare workers, and are challenging to manage within environments such as neonatal units. This study highlights the utility of whole-genome sequencing in identifying and mapping an outbreak. It is recommended that targeted staff screening should be considered early in similar outbreaks. In this setting, mass suppression therapy was not an effective strategy despite a high level of staff engagement and compliance.